LITERACY INFORMATION ON INDONESIAN LANGUAGE TEACHERS AND THE DEVELOPMENT OF FUTURE TEACHER BOOKS - Titik Harsiati (Jurusan Sastra Indonesia, 2021)
This article aims to describe (a) Teacher's Book Encourages Information Literacy and (b) Teacher's book Encourages the Improvement of Creative Critical Thinking Ability. The teacher's book contains a variety of information, from the procedures for using the book, the substance of learning materials, to comprehensive literacy content. In addition, the book must also be able to guide the teacher to be able to select and apply learning materials and strategies according to the times and needs of students. In addition, the book must also be able to guide teachers in order to grow and improve students' critical thinking skills and attitudes.Keywords: literacy information, teacher’s book, creative-critical thinking ability.